Democracy's dangers & discontents the tyranny of the majority from the Greeks to Obama - Thornton, Bruce S. (Hoover Inst. Press, 2014)
By democracy we usually mean a government comprising popular rule, individual human rights and freedom, and a free-market economy. Yet the flaws in traditional Athenian democracy can instruct us on the weaknesses of that first element of modern democracies shared with Athens: rule by all citizens equally. In Democracy's Dangers & Discontents, Bruce Thornton discusses those criticisms first aired by ancient critics of Athenian democracy, then traces the historical process by which the Republic of the founders has evolve
Includes bibliographical references (p. 171-176) and index
Foreword / Victor Davis Hanson -- Introduction: The Triumph of Democracy and the Antidemocratic Tradition -- 1. The Monitory Failures of Athenian Democracy -- 2. The Antidemocratic Tradition and the American Founding -- 3. Democracy and Leviathan -- Conclusion: Restoring Limited Government
Keywords: Geschichte; Democracy; Demokratie